Structural change of production and consumption: A micro to macro approach to economic growth and income distribution - Tommaso Ciarli; André Lorentz; Maria Savona; Marco Valente (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
We propose a theoretical model/framework for the analysis of the concomitant effects of structural changes in both production and consumption, on long run economic growth and income distribution. To accomplish with such a broad aim, we develop an evolutionary model with agentbased microfoundations. At the core of the model we take into account: (i) firmlevel organisational structure and technological changes; (ii) the impact of technology and organisation on the structure of earnings and income of workers/consumers; and (iii) the consequent changes in consumption patterns. The model thus articulates the links between production and organisation structures on the supply side, and the endogenous evolution of income distribution and consumption patterns on the demand side. We first analyse the model's properties, via numerical simulations, for a given setting of the structural conditions; we graphically show that the main determinants of endogenous economic growth and takeoff are the structural variables. We then analyse the space of the parameters that determine the structural conditions; simplified scenarios are identified via numerical simulations, in which patterns of aggregate growth are obtained as an emerging property of different structures of firms' organisation and production, functional composition of employment, income distribution and patterns of consumption.
Keywords: O12; J31; L23; D11; O41; 330; structural change; consumption; earnings distribution; growth; Bruttoinlandsprodukt; Gesamtwirtschaftlicher Konsum; Strukturwandel; Technischer Fortschritt; Organisatorischer Wandel; Wirtschaftswachstum; Einkommensverteilung; Agentenbasierte Modellierung; Theorie